A comparative study on the activities of six combination regimens against multidrug-resistant Mycobacterium tuberculosis infection in BALB/c mice. (1st April 2013) - Zheng, Meiqin; Jin, Haixia; Fu, Lei; Xu, Jian; Wang, Bin; Zhao, Weijie; Zhu, Hui; Li, Peng; Lu, Yu; Li, Qi
Abstract : The objective of the present study was to compare the activities of six combination regimens in a murine tuberculosis model infected with a multidrug-resistant tuberculosis isolate. After 1 month of treatment, all the combination regimens dramatically reduced CFU counts in the spleens and lungs, especially the regimens containing six drugs which had no visible counts in either organ. After 2 months of treatment, the spleens of mice treated with the six regimens all became culture negative, but for the lungs, only those treated with the regimens containing six drugs became culture negative. When levofloxacin was replaced by moxifloxacin, the regimen displayed a better activity. The activity of amikacin is closely related to the dosage. Despite in vitro resistance, isoniazid showed moderate activity. Clofazimine was able to improve the combination therapy results. Three months post-treatment, both the spleens and lungs of mice treated with the two regimens containing six drugs remained culture negative, while the spleens of mice treated with the other four regimens became culture positive. The activity of the regimens improved as more drugs were added.